ADMINISTRATIVE INFORMATION SYSTEMS DESIGN BEAUTIFUL RESTAURANT TOUR - Risman Risman; Drs. Soetirto Sadikin. M.A (Jurnal Sistem Informasi, 1999)
Satisfactory service is the key to business done wonderful tourist restaurants. One ofthe restaurant management efforts to meet these demands is to build informationsystems that can handle sales, handling of inventory until the purchase of rawmaterials, so the restaurant will be increasing productivity.To meet these needs, the author conducted the analysis and design of administrativeinformation system that handles its restaurant sales, purchasing, accounts payable andinventory handling. The research which writer to do is to read books and otherreading as a source of information. Moreover, I also do research directly to the fieldin a way mewancarai the parties involved to get their feedback about restaurant workprocedures.The result is known that the administration system of integrated computer-basedrestaurant can meet the needs of beautiful tourist restaurant management.